The Innovation of Maruo's Popup Book to Help Children with Special Needs in Memorizing Alquran - Amani, Risca; Luthfi, Afdal; Qomari, Vikri Aflaha; Mahdi, Arisul; Langputeh, Sukree (Khalifa Journal of Islamic Education, 2021)
Children with special needs have a particular way of learning which requires media to learn Alquran. This article discussed how a media developed for Alquran learning for children with special needs was created. This study discussed the design of Alquran Learning Media for children with special needs in memorizing Al-Qur'an. Hence, the prototype method was utilized in this study implemented by identifying problems, analyzing user needs, designing products according to user needs, making products that have been planned, validating experts, and product testing. To get an acceptable result, the author collected sources for the literature from the primary ones such as reports, results of previous research, to expert opinions to conduct this learning media. After testing the media, the overall analysis results showed that Mauro's popup book can be used as a medium to help memorize the Alquran for children with special needs, especially children with autistic disorders. In other words, this product can be adopted as a solution for children with special needs to help them in memorizing Alquran